NANOCRYSTAL TECHNOLOGY: INCREASING ORAL BIOAVAILABILITY OF LOW-SOLUBLE DRUGS - Yağmur Pirinçci Tok; Sevgi Güngör; Yıldız Özsoy Erginer (Sabiad)
Nanocrystal technology enables the production of solid drug particles with a particle size below 1000 nm without the need for any carrier system. By reducing the size of the particles of drugs with low solubility in water, increasing the surface area and decreasing the thickness of the diffusion layer leads to an increase in k the solubility rate. Accordingly, the increasing concentration gradient in the absorption zone promotes permeation and absorption by passive diffusion between the intestinal lumen and blood. Therefore, it is very important to improve and / or increase their bioavailability by using the nanocrystal technology approach for drug molecules belonging to BCS Class II and IV. Top-down and bottom-up methods are used to obtain nanometer-sized drug particles. In the pharmaceutical industry, top-down methods, which are subdivided into wet milling (BWM) and high pressure homogenization (HPH), are preferred in the ball mill because of its ease of application, repeatability and scalability. With nanocrystal technology, it is aimed to create new dosage forms by providing less side effects, lower doses and faster onset of action of drug molecules that are already approved in the pharmaceutical industry. It is also aimed that new drug molecules can be formulated with better bioavailability.